Development of Augmented Reality-Based Science Module to Find Out the Understanding of Grade IX Junior High School Students on Pressure Concepts - Iwel Triana; Siti Nurul Khotimah (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop an Augmented Reality (AR)-based science module to improve students’ understanding of pressure concepts. The development was motivated by students’ low interest and difficulty in learning abstract pressure concepts, as well as the limited availability of interactive instructional media. The research employed the ADDIE development model and implemented a one-group pretest–posttest design to evaluate the module’s effectiveness. The AR module was designed based on curriculum requirements and student characteristics, followed by the creation of 3D visualizations and integration into an AR application. Validation by material and media experts indicated a very good level of feasibility (mean score 4.78 on a 5-point scale). The module was implemented with Grade IX students at SMP Surya Kencana Bhakti, Bandung. Results showed an increase in the average score from 36.79 (pretest) to 75.71 (posttest). The normalized gain (N-gain) was 0.62, which falls into the Medium category according to Hake’s criteria. The improvement was statistically meaningful, and more than 90% of students reported higher motivation and engagement. Overall, the AR-based module is considered feasible and effective, making it a suitable interactive learning resource for supporting science learning in the 21st century.